2016
DOI: 10.1155/2016/4371367
|View full text |Cite
|
Sign up to set email alerts
|

Management of a Low-Energy Penetrating Brain Injury Caused by a Nail

Abstract: Low-energy penetrating nail injury to the brain is an extremely rare neurosurgical emergency. The most common cause of nail gun injury is work related accidents; other causes result from accidental firing of a nail gun, suicide attempts by firing nail guns into the brain, and bomb blasts containing pieces of nails. Neurosurgical treatment performed by craniotomy still seems to be the safest one; there are reports of complications such as subdural hematoma and intraparenchymal hemorrhages following the blind re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 11 publications
2
15
0
Order By: Relevance
“…Although blind retrieval can be used to remove nails with heads outside of the skull, 17 , 27 , 28 complications, including delayed ICH, have been reported in several studies. 17 , 27 31 Therefore, craniotomy is strongly recommended for debridement and hematoma examination in cases of embedded nails.…”
Section: Discussionmentioning
confidence: 99%
“…Although blind retrieval can be used to remove nails with heads outside of the skull, 17 , 27 , 28 complications, including delayed ICH, have been reported in several studies. 17 , 27 31 Therefore, craniotomy is strongly recommended for debridement and hematoma examination in cases of embedded nails.…”
Section: Discussionmentioning
confidence: 99%
“…Head CT scans clearly showed that no important functional areas or structures were damaged; neuroimaging is crucial in any penetrating head injury. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…Neurosurgical treatment performed by craniotomy still seems to be the safest one; there are reports of complications such as subdural hematoma and intraparenchymal haemorrhages following the blind removal of foreign bodies leading to suggestions that all penetrating foreign bodies should be removed under direct vision. 3 Prognosis of patients with penetrating injuries to the brain generated by objects with low kinetic energy is good and they have a better outcome. After taking informed written consent, patient was shifted to the neurosurgical operating room Standard American Society of Anaesthesiologists (ASA) monitors were attached and baseline vitals were recorded.…”
Section: Pathological Discussionmentioning
confidence: 99%